Pengaruh Implementasi Kebijakan Sistem Informasi Manajemen Penyuluhan Pertanian dan Biaya Operasional Penyuluh terhadap Kinerja Penyuluh Pertanian pada Dinas Pertanian Provinsi Jawa Barat - Dini Andriyani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study examines the influence of the Agricultural Extension Management Information System (SIMLUHTAN) implementation and Operational Cost Support (BOP) on the performance of agricultural extension workers in West Java Province. The main issue addressed is the suboptimal performance of extension workers due to limited digital literacy, infrastructure constraints, and insufficient operational support. The study aims to analyze both partial and simultaneous effects of SIMLUHTAN implementation and BOP on extension performance. A quantitative explanatory approach was employed using a survey method. Data were collected through structured questionnaires from 112 agricultural extension workers selected from a population of 2,784 using proportional sampling. The data were analyzed using multiple linear regression supported by SPSS, along with classical assumption tests. The results indicate that SIMLUHTAN implementation has a positive and significant effect on performance (34.1%), while BOP contributes 28.7%. Simultaneously, both variables explain 38.6% of the variance in performance. These findings suggest that improving system utilization and ensuring adequate operational support are essential to enhance extension workers’ performance. Strengthening training and infrastructure is also recommended to optimize the benefits of digital-based extension systems.